Homogeneous catalysed hydrogenation of HMF - Cadu, Alban; Sekine, Kohei; Schaub, Thomas; Hashmi, A. Stephen K. (Green chemistry, 2018)
In this report, hydroxymethylfurfural (HMF) is used as a bio-based feedstock for homogeneous metal-catalysed hydrogenation. Several ligand classes and metals are employed to reduce the aldehyde and aromatic ring of HMF. The previously unknown homogeneous catalysed hydrogenation of HMF to tetrahydrofuran-dimethanol (THFDM) was investigated using different catalyst systems. NHCs and phosphites give higher trans/cis ratios (between 1 : 1.25 and 1 : 3.95) of the product THFDM, but low conversions of only up to 17% accompanied by up to 92% yield of bis(hydroxymethyl)furan at 10 bar H2 and 120 °C. Conversely, di-phosphine ligated ruthenium catalysts in up to 87% yield lead to the highest overall conversion but only moderate trans/cis ratios of only 1 : 3.1-1 : 5.